Cholangiocarcinoma Seeding along a Ventriculoperitoneal Shunt Catheter: A Rare Initial Manifestation - Morais, Barbara Albuquerque; Iglesio, Ricardo Ferrareto; Petitto, Carlo Emanuel; Pinto, Fernando Campos Gomes; Teixeira, Manoel Jacobsen (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Cholangiocarcinoma accounts for less than 2% of all malignant neoplasms. Its cutaneous metastases are extremely rare, accounting for 0.0002% of all cases. The ventriculoperitoneal (VP) shunt has been considered a potential route for tumor dissemination. This type of tumor proliferation has been well documented in patients with intra-abdominal metastases secondary to brain tumors and, less frequently, brain metastases secondary to intra-abdominal tumors. In spite of that, there are few reports of cutaneous metastases along the VP shunt catheter trajectory.We present the case of a cholangiocarcinoma cutaneous metastasis at the VP shunt trajectory as the first clinical sign of this type of tumor. The patient had undergone the shunt insertion 4 years earlier due to a hydrocephaly secondary to a subarachnoid hemorrhage. After diagnosis, she was referred to chemotherapy and oncology follow-up.In the literature, 30 cases of cutaneous metastasis of cholangiocarcinoma were reported. Dissemination has been described involving percutaneous biliary drainage and distant sites. However, the case presented in this study alerts us about the possibility of cutaneous metastasis of intra-abdominal tumors in the trajectory of VP shunt catheters.
Keywords: cholangiocarcinoma; ventriculoperitoneal shunt; cutaneous metastasis